Evaluasi Metode Bimbingan Keagamaan dalam Meningkatkan Kecerdasan Spiritual Anak - Tasya Anggraini; Hidayani Syam; Akbar Hidayat; Rokhia Lamesa (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Research This study evaluates the method of religious guidance in improving children's spiritual intelligence of children at the Cilinaya Institute. This study uses the method of library research with a qualitative approach to analyze the urgency of religious moderation in the context of globalization. to analyze the urgency of religious moderation in the context of globalization. Data was obtained from various literatures, such as books, journals and related articles. The evaluation results show that children's spiritual intelligence can be improved through a structured, sustainable and values-based approach. religion. This finding underscores the importance of strengthening religious guidance as a efforts to develop dimensions of religiosity that include ideological aspects, intellectual, ritual, experience, and consequences in daily life.